Adaptations and modifications to a co-designed intervention and its clinical implementation: a qualitative study in Denmark - Jeanette Wassar Kirk; Per Nilsen; Ove Andersen; Nina Thórný Stefánsdóttir; Birk Grønfeldt; Rasmus Brødsgaard; Britt Stævnsbo Pedersen; Thomas Bandholm; Tine Tjørnhøj-Thomsen; Mette Merete Pedersen (BMC, 2021)
Abstract Background There is a long-standing debate in implementation research on whether adaptations to evidence-based interventions (EBIs) are desirable in health care. If an intervention is adapted and not delivered as conceived and planned, it is said to have low fidelity. The WALK-Cph project was developed based on the assumption that involving stakeholders in co-design processes would facilitate the fidelity of an intervention to increase the mobility of acutely admitted older medical patients and its implementation in two hospitals in Denmark. The purpose of this study is to describe and analyse adaptations and modifications that were made to the co-designed WALK-Cph intervention and its implementation. Methods This study used a qualitative design. An ethnographic field study was performed using participant observations, workshops and semi-structured interviews. Data were analysed twice using the Framework Method. The first analysis was based on the frameworks from Stirman, Moore and Proctor. The second analysis, a retrospective modifications analysis, was based on the Adaptation-Impact Framework. Results Many different types of adaptations and modifications were made to the WALK-Cph intervention and its implementation plan. Most of the modifications were made on the contents of the intervention. In total, 44 adaptations and modifications were made, of which 21 were planned (adaptations) and 23 were made haphazardly (modifications). Most of the content and context adaptations and modifications made on the intervention had a mixed result regarding enhanced fidelity. The retrospective modifications analysis showed that modifications were ongoing and both situationally and contextually shaped. Conclusions Although an extensive co-design process was carried out to facilitate the fidelity of the WALK-Cph intervention, this study showed that many adaptations and modifications were still made to both the intervention and its implementation plan. It could indicate that the co-design process had a small effect or that adaptations and modifications are ongoing and both situationally and contextually shaped, which challenge the assumption and the desire to be able to plan and control changes.